Digital Marketing Strategy Wedding Planning Tools in Indonesia - Rahmah, Rosyidah; Setiawan, Margareth (Forum Kerjasama Pendidikan Tinggi, 2023)
This article will give the analysis necessary to build a future digital marketing plan for Jangji, whose primary purpose is to acquire new customers on the Indonesian market. Jangji is one of the many small and medium-sized enterprises in Indonesia that is still seeking to establish a successful digital marketing strategy. The following analyses will be examined in depth. First, both external and internal research is conducted to determine the company's current market position. Second, conduct empirical research to determine the most crucial factors for wedding planners and businesses. Eleven Indonesian users of wedding planning tools receive a Google form-based semi-structured interview as part of a qualitative study methodology. This information will assist in analyzing and determining the optimal digital marketing strategy decisions. In addition, wedding planners and businesses in Indonesia that specialize in the wedding industry will be able to expand their customer base and brand recognition with the help of these findings.